The Effectiveness of Psychoeducational Group Therapy to Motivate Change Among Addicts in the Early Stages of Change - Mohd Rafidi Bin Jusoh (Universiti Sains Islam Malaysia, 2024)
This research aims to study the effectiveness of psychoeducational group therapy in increasing the motivation of drug addicts who are at the early stage of change as they are undergoing treatment and rehabilitation at a rehabilitation institution, Cure and Care Rehabilitation Center (CCRC), in Jelebu, Negeri Sembilan. Based on the construct of the Transtheoretical Model of Behavioral Change (TTM), the psychoeducational group therapy module was developed by the researcher by using the processes of change as the basis of sessions and activities. Before it was used, the module was first tested for its validity and reliability. Three dependent variables were measured to study the motivational changes, namely stages of change, self-efficacy and decisional balance. This research applied the experimental design or the pretestposttest control group design, with an additional follow-up test. Through this design, the effects of treatment were viewed using the within-subjects design and betweensubjects design for pretest, posttest and follow-up test. The research sample was selected using the purposive random sampling method which fulfilled the treatment duration criteria and the pre-determined stage of change. 45 inmates agreed to participate in the research. They were randomly divided into four experimental groups, namely treatment-naïve experiment group (PGTN), treatment-experienced experiment group (PGTE), treatment-naïve control group (CGN), and treatmentexperienced control group (CGE). Two of the experiment groups (PGTN and PGTE) went through 15 sessions of therapy for 60 to 90 minutes each and treatment as usual, while the control groups (CGN and CGE) only received the usual treatment. Three measuring instruments, Stages of Change Scale (SoCS), Self-Efficacy Scale (SES) and Decisional Balance scale, were used. Three levels of tests were conducted using these instruments at the pretest, posttest and follow-up stages. The data obtained were analysed using statistical test analysis, one-way repeated measures ANOVA and covariance (ANCOVA). The research findings showed that psychoeducational group therapy was effective in increasing the motivation of experienced addicts who were at the early stage of change, with an improvement of at least one stage ahead, an increase in self-efficacy stage and decisional balance compared to before the treatment. All these remained even after the follow-up test was conducted. As for the naïve addicts group, an increase in motivation was only discovered in the decisional balance change. Nevertheless, the follow-up test showed that the therapy was effective in increasing the motivation of all experimental groups (PGTN and PGTE) compared to the control group, as shown in an increase in the statistic score. Based on these research findings, the rehabilitation module based on the psychoeducational approach that applied the group therapy was effective in increasing the motivation of addicts who were going through treatment and rehabilitation at a rehabilitation institution. The main implications of the research findings and several recommendations for future research are also discussed.